Efeito do reuso sobre as características de superfície e da composição química de instrumentos de NiTi - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Endodontic instruments NiTi were analyzed using a Scanning Electron Microscope (SEM) coupled to a Spectrometer X-ray by Energy Dispersive (EDAX), before and after use, in order to assess the presence of defects, deformations and analyze its chemical composition. To this end, thirty instruments were divided into 3 groups, 10 Protaper Next®X1 files (PNX1), 10 Protaper Next®X2 files (PNX2) and 10 WoveOne® files (WO), which were electromicrograph 250-fold increase in tip region, the tip of 2mm and 4mm. The instruments were used in the preparation of 60 simulated canals blocks made of polyester resin. Initially we performed the catheterization with K file # 10 and the length (CT), followed by instrumentation according to each group. Group 1: 10 blocks of simulated canals were instrumented with ProTaper NEXT® system using the file X1 to instrumentation of the cervical and middle third and X2 to the apical third. Group 2: 10 blocks were instrumented with the WaveOne® 25.08 Primary file system according to the manufacturer's recommendations. The instruments were first used one time and then reused 2 times, always in new simulated channels. The files were washed in ultrasonic tank and subjected to new microscopic analysis by SEM and EDAX. Then the elétromicrografias were taken at the tip of the instrument, the tip of 2mm and 4mm, with an increase of 250X. To establish the scores were observed the presence of jagged edges, grooves, wells and burrs. Each instrument when compared with each other in the same length over the three days of use showed no statistical difference in relation to the increase in defects (p> 0.05). Regarding the scores, statistical analysis of the results showed that only WO files showed a higher number of defects and deformations in the length of 4mm, the third time evaluation of the study (p <0.05). It has been observed in the analysis of the chemical elements that PNX1 files showed significant losses compared to the average Ni before use and after the third application (p <0.01); PNX2 the files and WO significant loss of Ni in the three days of use (p <0.01). Regarding Ti, PNX1 files in no significant loss during use (p> 0.05), but the files PNX2 showed significant loss between before and the first instrumentation and between the first and third use (p <0, 01). In WO files, a significant loss when compared before and after the first use and prior to the third use. Thus, reuse demonstrated that the instruments had all defects and deformations at some length and time of the study but not increased with use. Loss occurred only in ProTaper Ni NEXT® X1 files after use and the ProTaper files NEXT® X2 and WaveOne® was no loss of Ni and Ti after 3 uses.
Keywords: Endodontia; Instrumentos odontológicos; Microscopia; Endodontics; Dental instruments; Microscopy; CIÊNCIAS DA SAÚDE: ODONTOLOGIA